(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This study delves into the realm of customer attitudes towards sales promotion strategies in Visakhapatnam City, employing the functional theory of attitudes as the guiding framework. Sales promotion, a key component of marketing efforts, aims to stimulate immediate customer action and boost sales by offering incentives and creating a sense of urgency. The research highlights the importance of sales promotion in marketing, emphasizing its role in creating awareness, differentiating brands, building customer loyalty, and accelerating the buying process. Drawing on the functional theory of attitudes, the study identifies four main functions that attitudes serve in influencing customer behaviour: utilitarian, knowledge, social-expressive, and ego-defensive. By exploring these functions, the paper provides a comprehensive understanding of the underlying motivations and needs driving customer responses to sales promotion strategies. The research methodology involved collecting quantitative data from 500 respondents in Visakhapatnam City through surveys. The data was analyzed using factor analysis and inferential statistics to draw meaningful conclusions and test hypotheses. The findings reveal significant differences in customer attitudes towards sales promotion strategies based on demographic characteristics such as age, gender, employment status, educational qualification, family income, and marital status. Moreover, customer preferences for media channels impact their attitudes towards sales promotions, with an omni-channel approach proving crucial for reaching and engaging diverse customer segments effectively.